The Outsiders - Hinton, S. E.; Fyfe, Jim; Listening Library; Random House Audio Publishing (New York : Listening Library/Random House Audio, 2006)
The struggle of three brothers to stay together after their parent's death and their quest for identity among the conflicting values of their peers.
Keywords: Family life -- Juvenile fiction; Gangs -- Juvenile fiction; Brothers -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Family life -- Fiction; Gangs -- Fiction; Brothers -- Fiction; Identity -- Fiction; Children's audiobooks; Children's audiobooks